Influence of the Mesoporous Polymer Matrix Nature on the Formation of Catalytically Active Ruthenium Nanoparticles - Mikhail Sulman; Valentin Doluda; Maksim Grigoryev; Oleg Manaenkov; Anastasiya Filatova; Vladimir Molchanov; Alexander Sidorov; Alexey Bykov; Irin Shkileva; Aleksandrina Sulman; Barry Stein; Valentina Matveeva (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
This paper reports on ruthenium nanoparticles formation and stabilization by hypercrosslinked poly-styrene and the catalytic properties of the nanocomposites obtained. Hypercrosslinked polystyrene with functional groups and without them was used. The nanocomposites were characterized using low-temperature nitrogen physisorption, X-ray photoelectron spectroscopy and transmission electron mi-croscopy. It is established that the tertiary amine group of the support influences both formation of ru-thenium nanoparticles, and their catalytic properties in the selective hydrogenation of D-glucose. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).